Human rights and COVID-19 triage: a comment on the Bath protocol. Issue 7 (16th April 2021) - Bhatt, Vivek; Michalowski, Sabine; Wyllie, Aaron; Kuylen, Margot; Martin, Wayne
Abstract : In their discussion paper of November 2020, Cook et al present a draft protocol for navigating circumstances in which emergency services are overwhelmed. Their paper suggests that COVID-related triage decisions should be based on clinical assessment, patient and family consultation, and a range of ethical considerations. In this response, we note that the protocol exhibits an ambiguity that is likely to result in irresolvable dilemmas when put into practice. This ambiguity is exemplified in the paper's prime ethical imperative (to 'save more lives and more years of life'), which takes the form of an undefined conjunction whose practical implications are left unspecified. We see this ambiguity in the prime imperative as one manifestation of a broader set of tensions in the protocol. We show that the discipline of human rights provides an essential supplement to the ethical framework on which Cook and colleagues rely, providing a framework for understanding and working through triage dilemmas involving age, discrimination and equality.